Graphic Histories of Solidarity, in Solidarity - Benson, Koni (Kronos, 2024)
Revolutionary experiments require building revolutionary relationships. This praxis of material and social creativity to reorganise power dynamics and weave connections across weaponised divides, are evident in the content, the form and the backstory woven into Janet Biehl's Their Blood Got Mixed: Revolutionary Rojava and the War on ISIS. Written and illustrated by Janet Biehl, it is a graphic memoir that can be read as both an historical narrative and a blueprint of a contemporary revolutionary experiment that combines political theory and graphic art to tell the story of how ISIS has been driven back in Northern Syria by people fighting for a society based on principles of direct democracy, political secularism, gender equality, and ecological sustainability. Whereas in the past, after the liberation of Rojava in 2012, Biehl spent time interviewing leadership, this book relays her interviews with women across the region and across the various projects of reorganising and defending social, political, cultural and economic life in 2019 after four years of warfare against ISIS and the Turkish state. Reflecting on the relationships that make revolutionary history, and that produce artistic histories of revolutionary experiments, this review article considers the history in this book and of this book, in conversation with recently published graphic non-fiction, and draws on engaged scholarship concerned with the politics of collective knowledge production in and for movements of solidarity urgently needed in the face of the imploding crisis of colonial borders.